Coupled Eulerian–Lagrangian simulation of granular medium sheet forming process and experimental ınvestigation at elevated temperature. Issue 9 (February 2017) - Liu, Kangning; Lang, Lihui; Zhang, Wenshang; Marai, Murhaf; Liu, Baosheng
Abstract The granular medium forming process is a newly proposed flexible die forming technique. It is mainly applied to fabricate thin-walled lightweight components such as titanium alloys and high-strength steel parts at relatively high temperatures (above 500 °C) with good forming quality. In order to investigate the flow behavior of the granular medium in the forming process, tri-axial compression test with different confinement pressures is performed. Test shows that the selected granular medium exhibits pressure-dependent properties with low-friction angle. Then, three classical geotechnical models, i.e., the Mohr–Coulomb, Drucker–Prager, and Duncan–Chang models are established for the numerical simulation process with the parameters obtained from the tri-axial compression test. To avoid the undesired mesh distortion during FEM simulation of forming process, Coupled Eulerian–Lagrangian (CEL) analysis method is developed. This enables the simulation of granular material involving large deformation. Finally, the granular medium forming experiment is implemented at 500 °C using commercially pure TA1 titanium sheet, and comparison study with the FEM simulation is carried out. Result indicates that the Mohr–Coulomb model exhibits the best performance regarding the calculation accuracy of shape dimension and thickness distribution.